PENGARUH EDIBLE COATING KITOSAN & EKSTRAK DAUN ANGGUR TERHADAP AKTIVITAS ANTIOKSIDAN DAN KADAR FLAVONOID BUAH ANGGUR - Trisna Ardiana Fatmawati; Eni Purwani; Aan Sofyan (Jurnal Teknologi Pangan dan Hasil Pertanian, 2025)
Chitosan-based edible coating is a thin, consumable layer derived from crustacean shells that functions as a natural preservative. The incorporation of grape leaf extract can enhance its antimicrobial and antioxidant properties, thereby improving the shelf life of food products. This study aimed to evaluate the effect of grape leaf extract addition to chitosan-based edible coating on the antioxidant activity and flavonoid content of red grapes during storage at room temperature. Extract concentrations of 0%, 3%, 4%, and 5% were applied, with measurements conducted on day 0 and day 7 of storage. Antioxidant activity was assessed using the DPPH method, while flavonoid content was measured via UV-Vis spectrophotometry. Results indicated a significant increase in antioxidant activity on day 0, with the highest value observed at 5% concentration (75.09%; p = 0.044). By day 7, antioxidant activity showed a tendency to increase, peaking at 76.30%, although the change was not statistically significant (p = 0.081). Flavonoid content increased significantly on both day 0 (p = 0.027) and day 7 (p = 0.000), with the highest levels recorded at 5% concentration (440.33 mg QE/g and 374.76 mg QE/g, respectively). Two-way ANOVA analysis revealed that both independent variables had a significant effect on the two parameters, while their interaction was significant only for flavonoid content (p = 0.000).